The Effect of Fresh Fruit Bunch Prices and Transportation Costs on The Income of Oil Palm Farmers in Kampung Rakyat District - T. Muhammad Arif; Novrihan Laily Nasution; Meisa Fitri Nasutio (Publisher Cv. Inara Colaboration with www.stie-sampit.ac.id, 2026)
This study aims to analyze the effect of Fresh Fruit Bunch (FFB) Prices and Transportation Costs on the Income of Oil Palm Farmers in Kampung Rakyat District, South Labuhanbatu Regency. This study uses a quantitative approach with multiple linear regression analysis methods. The study population was 1,250 oil palm farmers with a sample of 93 respondents determined using the Slovin formula with a 10% error rate. Data were collected through questionnaires, structured interviews, and field observations, then analyzed using SPSS version 25 at a significance level of 5%. The results showed that partially, the FFB Price had a positive and significant effect on the income of oil palm farmers with a significance value of 0.017 < 0.05 and a regression coefficient of 0.180. This indicates that an increase in the price of FFB will increase farmers' income. Meanwhile, Transportation Costs did not have a significant effect on farmers' income with a significance value of 0.944 > 0.05, although the regression coefficient was negative. Simultaneously, the FFB Price and Transportation Costs had a significant effect on the income of oil palm farmers. The coefficient of determination (R²) of 0.362 indicates that the two variables are able to explain 36.2% of the variation in farmers' income, while 63.8% is influenced by other factors outside the research model. Based on the research results, it can be concluded that the price of fresh fruit bunches (FFB) is the most dominant variable in influencing the income of oil palm farmers in Kampung Rakyat District. This research is expected to be a consideration in formulating policies to improve the welfare of oil palm farmers.